Dampak Pendidikan Multikultural Diberikan kepada Siswa Dalam Meningkatkan Rasa Nasionalisme dan Sikap Toleransi Atas Perbedaan di Lingkungan Sekolah:: Studi Kasus di SMP Negeri 27 Medan Kelas IX-5 - Daulay, Nadia Saputri; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Siagian, Nancy Octavia; Betsya, Della; Damayanti, Putri; Clever, Desswan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This examination expects to decide the effect of multicultural training given to understudies in expanding a feeling of patriotism and a mentality of capacity to bear contrasts in the school climate. For this situation, schools need to do exchange by putting each current social development on fair terms. Second, schools need to foster resilience to give chances to each culture to see one another. The examination utilized by the creator is subjective exploration, where the exploration is completed in a smaller however more top to bottom extension. To carry out this, the job of instructors is extremely fundamental since they can assist with imparting life esteems so they can frame characters that reflect public personality. In this examination we incorporated a few respondents comprising of Pancasila Training subject educators, direction and guiding educators and understudies of Medan 27 State Center School in class IX-5. The outcomes we got were that at SMP Negeri 27 MEDAN in class IX-5, 89% of understudies and educators were carrying out multicultural training and practically all understudies and instructors had a feeling of patriotism and a demeanor of capacity to bear contrasts in the school climate. Despite the fact that there were still A few understudies have not taken on a mentality of resilience and a feeling of patriotism in the school climate. So a few arrangements are expected to work on multicultural training in study hall learning. Watchwords: Resilience, Multicultural Instruction, School